2017
DOI: 10.1136/rmdopen-2017-000588
|View full text |Cite
|
Sign up to set email alerts
|

Real-world burden of comorbidities in US patients with psoriatic arthritis

Abstract: ObjectivesWe assessed comorbidities associated with psoriatic arthritis in a broad cohort of US-insured adult patients using the Truven Health Analytics MarketScan Database.MethodsPrevalence and incidence rates were assessed for 28 comorbid conditions among adult patients in the MarketScan database with a diagnosis of psoriatic arthritis and having two or more health claims for psoriatic arthritis between 1 July 2008 and 31 July 2015. Findings were compared with those of a similar, previously published analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 38 publications
2
37
0
5
Order By: Relevance
“…Extracutaneous comorbidities are also well-documented in PV, as individuals suffering from severe disease are at high risk of psoriatic arthritis, metabolic syndrome, and atherosclerosis (Burden and Kirby, 2016;Fang et al, 2016;Shah et al, 2017). Therefore, it has been proposed that PV is a systemic disease, manifesting with skin, joint, and vascular inflammation (Davidovici et al, 2010;Reich, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Extracutaneous comorbidities are also well-documented in PV, as individuals suffering from severe disease are at high risk of psoriatic arthritis, metabolic syndrome, and atherosclerosis (Burden and Kirby, 2016;Fang et al, 2016;Shah et al, 2017). Therefore, it has been proposed that PV is a systemic disease, manifesting with skin, joint, and vascular inflammation (Davidovici et al, 2010;Reich, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we discuss the prevalence of type 2 diabetes in patients with PsA. DM is among the most common metabolic disorders, with majority of patients (90-95%) affected by type 2 DM [12]. Few studies investigate the association between type 1 DM and other immune-mediated diseases including PsA, but they do not find any association [13].…”
mentioning
confidence: 99%
“…Is important to mention that our center has two years since it was opened so we expected to admit more patients and it is expected that the rates that we showed could change. This was the first study in Mexico that evaluated comorbidities, this is very important because there are other authors that have showed that comorbidities in psoriatic arthritis patients are an important burden in the health system [8,10]. Shah K et al [10], showed a prevalence rate of 35% of dyslipidemia, 31% of hypertension, 15% of depression and 13% of diabetes mellitus vs. 22, 31, 15 and 13% respectively.…”
Section: Discussionmentioning
confidence: 99%